2007
DOI: 10.1096/fasebj.21.5.a176-c
|View full text |Cite
|
Sign up to set email alerts
|

Long term exposure to high protein diet or high fat diet have opposite effects on vagal afferent sensitivity to lumenal macronutrients and ip cholecystokinin

Abstract: Long term exposure to high fat (HF), high protein (HP) or high carbohydrates (HC) diets may lead to alterations of short term control of food intake, especially through their effects on peripheral sensitivity to gut hormones such as cholecystokinin and macronutrients. METHODS: Mice were submitted to either HF, HP or HC diet for 2 weeks. Neuronal activation was measured within the first central relay of vagal ascending fibers, the Nucleus of the Tractus Solitarius (NTS) in response to either intragastric gavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Diets high in protein will elevate concentrations of plasma amino acids [ 54 ]. According to Nefti et al high intake of protein induces a vagal feedback to the satiety center of the nucleus tractus solitarius in the brainstem and the hypothalamus to suppress hunger [ 55 ]. Poppitt et al [ 56 ] showed that the satiating effect after a high-protein preload was significantly larger than preloads containing an iso-energetic amount of carbohydrates or fats.…”
Section: Introductionmentioning
confidence: 99%
“…Diets high in protein will elevate concentrations of plasma amino acids [ 54 ]. According to Nefti et al high intake of protein induces a vagal feedback to the satiety center of the nucleus tractus solitarius in the brainstem and the hypothalamus to suppress hunger [ 55 ]. Poppitt et al [ 56 ] showed that the satiating effect after a high-protein preload was significantly larger than preloads containing an iso-energetic amount of carbohydrates or fats.…”
Section: Introductionmentioning
confidence: 99%